Investment Decisions Under An Emissions Intensity Target - McMullan, Beth Mary (Curtin University, 2020)
This thesis reports the results of a controlled laboratory experiment to test the effect of emissions price certainty on firm investments in clean technology when a regulator has set an intensity target. As fixed prices are associated with emissions closer to predictions, policymakers concerned with meeting specific targets might be more inclined to use a tax. Alternatively, if lowering emissions is a greater priority, then the market mechanism may be favoured.